UJI AKTIVITAS ANTIDIABETES EKSTRAK DAUN PACAR AIR (IMPATIENS BALSAMINA L.) TERHADAP HEPAR TIKUS WISTAR JANTAN (RATTUS NORVEGICUS L.) YANG DIINDUKSI ALOKSAN - Mutiara Ema; Syukriah; Leni Widiarti (LPPM Universitas Cipta Mandiri, 2026)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia due to insulin deficiency or insulin resistance. Prolonged hyperglycemia can trigger oxidative stress and liver damage characterized by increased levels of SGOT and SGPT enzymes. This study aims to determine the effect of henna leaf extract (Impatiens balsamina L.) on SGOT and SGPT in alloxan-induced Wistar rats (Rattus norvegicus L.). The study used a completely randomized design (CRD) with six treatment groups and four replications, namely KN (normal control), K- (alloxan 150 mg/kg BW), K+ (alloxan + glibenclamide), P1 (alloxan + extract 450 mg/kg BW), P2 (alloxan + extract 500 mg/kg BW), and P3 (alloxan + extract 550 mg/kg BW). Data were analyzed using One Way ANOVA and Duncan's test. The results of the study showed that henna leaf extract had an effect on liver SGPT and SGOT levels in male white rats induced by alloxan. Henna leaf extract at a dose of 500 mg/kg body weight was proven to be effective in reducing SGPT and SGOT levels in rats induced by alloxan at 150 mg/kg body weight.